Transvaginal Ultrasound‐Guided Fine‐Needle Aspiration Biopsy of Pelvic Lesions. (13th May 2021) - Penna, Rubal; Poder, Liina; Jha, Priyanka; Seigel, Eliot L.; Morgan, Tara A.
Abstract : Objectives: To assess adequacy of transvaginal ultrasound‐guided fine‐needle aspiration biopsy (TVUS‐FNAB) for pathologic diagnosis of pelvic masses performed using onsite cytopathology consultation. Methods: In this Institutional Review Board approved, Health Insurance Portability and Accountability Act (HIPAA) compliant study, radiology records were retrospectively queried to identify patients who underwent TVUS‐FNAB of a pelvic mass over a 11‐year duration. TVUS‐FNAB adequacy was determined by correlating cytopathology results with transvaginal ultrasound‐guided core‐needle biopsy (TVUS‐CNB) or surgical pathology results when available, and with clinical diagnostic confidence when additional pathology confirmation was not available. Secondary analysis included patient age, history of hysterectomy, or pelvic malignancy. Target‐specific features analyzed included mass size, depth, location, and final pathologic diagnosis. Results: Sixty patients underwent TVUS‐FNAB of pelvic masses, 43 of which underwent FNAB only and 17 underwent both TVUS‐FNAB and TVUS‐CNB during the same procedure. TVUS‐FNAB alone was adequate for diagnosis in 51 (85%) cases and addition of core‐needle biopsy (CNB) achieved a diagnosis in additional 4 patients, increasing overall diagnostic accuracy to 92% (55/60). FNAB inadequacy had statistically significant association with increasing mass depth, occurrence of a minor intraprocedural complication, and decision to perform a CNB ( P <.05). Number of FNAB passes, mass size, history of hysterectomy, and final diagnosis were not statistically significant predictors of FNAB adequacy. Conclusion: TVUS‐FNAB has a high specimen adequacy rate when performed with an onsite cytopathologist and can be considered first‐line approach for image‐guided sampling of pelvic lesions with option to add CNB if preliminary cytopathologic review does not confirm sample adequacy. Abstract : Access the CME test here and search by article title.